The Critical Role of Spreading Depolarizations in Early Brain Injury: Consensus and Contention - Andrew, R. David; Hartings, Jed A.; Ayata, Cenk; Brennan, K. C.; Dawson-Scully, Ken D.; Farkas, Eszter; Herreras, Oscar; Kirov, Sergei. A.; Müller, Michael; Ollen-Bittle, Nikita; Reiffurth, Clemens; Revah, Omer; et al. (Neurocritical care, 2022)
Background When a patient arrives in the emergency department following a stroke, a traumatic brain injury, or sudden cardiac arrest, there is no therapeutic drug available to help protect their jeopardized neurons. One crucial reason is that we have not identified the molecular mechanisms leading to electrical failure, neuronal swelling, and blood vessel constriction in newly injured gray matter. All three result from a process termed spreading depolarization (SD). Because we only partially understand SD, we lack molecular targets and biomarkers to help neurons survive after losing their blood flow and then undergoing recurrent SD. Methods In this review, we introduce SD as a single or recurring event, generated in gray matter following lost blood flow, which compromises the Na + /K + pump. Electrical recovery from each SD event requires so much energy that neurons often die over minutes and hours following initial injury, independent of extracellular glutamate. Results We discuss how SD has been investigated with various pitfalls in numerous experimental preparations, how overtaxing the Na + /K + ATPase elicits SD. Elevated K + or glutamate are unlikely natural activators of SD. We then turn to the properties of SD itself, focusing on its initiation and propagation as well as on computer modeling. Conclusions Finally, we summarize points of consensus and contention among the authors as well as where SD research may be heading. In an accompanying review, we critique the role of the glutamate excitotoxicity theory, how it has shaped SD research, and its questionable importance to the study of early brain injury as compared with SD theory.